Enhancing Bread Quality: Investigating the Physicochemical and Sensory Properties of Bread with Sweet Potato Flour and Okra Hydrocolloids as Substitutes for Wheat Flour - António Paulo Machine; Armando Abel Massingue; Simião Gabriel Balane; Egas José Armando (Current Perspectives in Agriculture and Food Science Vol. 8, 2024)
In order to enhance the bread qualities, the effects of partial substitution for wheat flour with sweet potato flour and the incorporation of aqueous okra hydrocolloid extract, on the physicochemical and sensory characteristics of wheat bread processing was evaluated. Bread is one of the oldest artificial basic human foods that have served man from the ancient days till present and its socio-economic importance cannot be undermined. It is also believed to be the most complete and cheap food and basic auxiliary food in times of extreme food poverty. Six breading formulations were prepared with the substitution of 10, 20 and 30% wheat flour for sweet potato flour with or without incorporation of aqueous okra hydrocolloid extract of 0.5, 1.0 and 1.5%, respectively. The physicochemical, proximate and mineral composition of the dough and breads were evaluated. Increased additions of okra hydrocolloid (OHC) and sweet potato flour (SPF) had a substantial impact on the CIE color of the bread and dough. Raising the SPF level reduced the dough’s baking yield whereas adding OHC increased it. The chemical makeup, pH, and titratable acidity of the loaves remained the same when WF was replaced with SPF and whether or not OHC was added. Sensory acceptance showed that wheat-sweet potatoes composite flour for bread production is still not usual for local consumers who assigned grades 6 and 7 with comments “I liked it slightly” and “I liked it moderately”. Results of the study indicate that SPF is a feasible alternative as a primary source material for bread production. It is concluded that the addition of sweet potato flour up to 30% in the production of bread is an interesting alternative to producing low cost bread without significant changes in its sensory and technological properties improving the nutritional value and “healthy” image of these products.